GEOLOGY OF SILIHWANGI AREA, MAJALENGKA DISTRICT, WEST JAVA PROVINCE - RADITYA RENDRA, PRADNYA PARAMARTA; Sukiyah, Emi (Journal of Geological Sciences and Applied Geology, 2019)
Silihwangi area is located in Majalengka District, West Java Province with coordinate 108°13’22” E - 108°16’5” E and 6°57’41” S - 7°0’22” S. This research aims to identifiy and know the geology of Silihwangi area and its surrounding. This research used digital maps to carried out processing step in studio and field equipment such as GPS, camera, compass, geological hammer, etc to carried out field observation. Some rock samples are taken for further analysis. Based on field observation and studio analysis, the research area can be divided into five morphology unit namely very gentle sloping hill, gentle sloping hill, rather steep hill, steep hill, and very steep hill morphology unit. Other than that, there are subparalel, radial, and subdendritic drainage pattern that can be found in the research area. The lithostratigraphic units in the research area, namely Sandstone (Tmbp), Claystone (Tpbl), Andesite intrusion (Ki), Tuff (Kt), and Volcanic breccia (Kbv) unit. Joint and lithology offset can be found in the research area.